The "Flint Depot" of prehistoric northern Israel: Comprehensive geochemical analyses of flint extraction and reduction complexes and implications for provenance studies. Issue 6 (13th February 2019) - Finkel, Meir; Barkai, Ran; Gopher, Avi; Tirosh, Ofir; Ben‐Yosef, Erez
Abstract: Recent research has demonstrated that the Eocene Timrat formation in northeastern Israel, which appears as an extensive land "strip" west of and parallel to the Rift Valley, was a major source of prehistoric flint. This supposition is supported by three large‐scale extraction and reduction (E&R) complexes identified within this region, which offer direct evidence of intense Lower and Middle Palaeolithic exploitation and limited Neolithic/Chalcolithic activities. Here, we present a first comprehensive overview of this "industrial strip" and of its E&R complexes (Nahal Dishon, Mt. Achbara, and Sede Ilan), demonstrating that these production areas were used mainly for the manufacture of large‐volume items such as Lower Palaeolithic hand axes, Middle Palaeolithic Levallois cores, and Neolithic/Chalcolithic axes/adzes. Furthermore, we integrate information from recently published field studies and lithic analyses with new intercomplex and intracomplex inductively coupled plasma mass spectrometry (inductively coupled plasma (ICP)‐MS) analyses of flint debitage. The relatively large number of analysed samples ( n  = 69) constitutes the first robust reference database for provenance studies of this E&R "strip." The potential contribution for provenance studies is demonstrated by a detailed ICP‐MS comparison drawn between specific extraction and reduction localities within the Dishon complex and flint tools found in six occupation sites located up to 20 km from the sources. The detailed geochemical study also yielded methodological insights regarding challenges associated with flint heterogeneity and patination effects.